Կապիտալի շահութաբերության ցուցանիշների կառուցվածքային համակարգը և նրա վրա ազդող գործոնների վերլուծությունը - Ալինա Բաբայան (ՀՀ ԳԱԱ հրատ.)
В статье сделана попытка на основе комплексного анализа структурной системы показателей рентабельности капитала обосновать пути повышения эффективности принятых решений по осуществлению длительных вложений в бизнесе с учетом позиции всех заинтерованных сторон (государства, собственников, кредиторов), оценкой рисков периодичности приоритетов, а также изучения процесса формирования источников финансирования.Based on complex analysis of the ROE the article attempts to justify the ways of increasing the effectiveness of decisions taken in implementation of the long-term investment in business, taking into account the positions of all stakeholders (government, owners, creditors), risk assessment of priorities periodicity as well as the study of formation process of sources of funding .
Keywords: Social Sciences; Economic Theory